ANALISIS KESULITAN DALAM PEMECAHAN MASALAH PEMBAGIAN - Frikson Jony Purba (Universitas Quality, 2021)
This study aims to analyze students' difficulties in solving division problems. This research was conducted in early September with the research location at SD Citra Kasih Cendana, Tanjung Morawa District. Data collection techniques in this study used tests and interviews. After analyzing the data on the results of the study, the calculation of the average grade IV SD Citra Kasih Cendana SD Tanjung Morawa District to understand the material division of Mathematics subjects obtained a value of 61.25 and was included in the Underprivileged category, Analysis of the learning difficulties of grade IV students in distribution material at SD Citra Kasih Cendana, Tanjung Morawa Subdistrict, the academic year 2020 is that students do not really like learning division operations, they do not understand the steps in carrying out the distribution, and there are still students who have not memorized the distribution so that students still experience difficulties in operations division. The factors that cause learning difficulties in fourth grade students in the distribution material at SD Citra Kasih Cendana, Tanjung Morawa District, the 2020 academic year are internal factors, namely talents and interests, motivation and enthusiasm for learning, hyperactivity and students do not understand the material well, while the external factor is the teacher. rarely checks or assesses student learning outcomes that students have done in class, and the teacher's way of teaching is still not appropriate in the learning they teach.